Teachers’ Strategy in Improving Students’ Learning Achievement of Al-Qur’an and Hadits at Madrasah Tsanawiyah - Mardiah Mardiah; Askar Askar; Rustina Rustina (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2020)
This study aims to determine the strategies of teachers of the Qur'an and hadith subjects in improving the learning achievement of students in Madrasah Tsanawiyah (MTs) Al-Khairaat Biromaru. The method is qualitative research, with data collection techniques namely; observation, interview and documentation. By using analytical techniques; data collection, data reduction, data presentation and data verification. Data verification uses three methods namely deductive, inductive and comparative. Research results show that by using expository learning strategies with lecture, training or group work methods in teaching it can make it easier for teachers to control students to learn in accordance with the objectives to be achieved in the Al-Khairaat Biromaru Madrasah (MTs) Al-Khairaat Biromaru namely to increase learning achievement. In addition, the selection of media in teaching is also highly considered by Madrasas, especially Madrasah Tsanawiyah (MTs) Al-Khairaat Biromaru because it is one of the determinants to motivate students so that their learning achievement increases, for example in the form of cardboard paper written by the teacher containing verses of Al-qur'an or hadith, or by showing videos that match the material.